Tank Battle And Trivia Quiz Games Development Using Construct 2 To Improve Critical Thinking Ability - Ariel Edmundo Han Kurniawan; Agus Cahyo Nugroho; FX. Hendra Prasetya (Soegijapranata Catholic University, 2023)
Game is something that is fun and entertaining 'of all time' and will always be in this world and can be enjoyed by both children, and adults. There are various types of games that are often played, including shooting and quiz games. Shooting Game has the main theme of shooting where players will beat each other to become the winner. While Quiz Game or often called Trivia Quiz is a game where players try to answer the questions given to get various kinds of prizes and become a winner. Construct 2 is a program for making games without writing programming code, because most of the game's logic can be arranged via the menu.This study aims to create a game design that is a combination of Shooting Game and Trivia Quiz where players can play both types of games simultaneously. While the program used is construct 2. And the sample used is 16 years and over. The methodology used is object-oriented design methodology. The modeling tools used are use case diagrams, activity diagrams and class diagrams. The results of making this game show that combining more than one type of game can be done and make a game more interesting.